2014
DOI: 10.1038/nbt.2892
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing of circulating tumor cells provides a window into metastatic prostate cancer

Abstract: Comprehensive analyses of cancer genomes promise to inform prognoses and precise cancer treatments. A major barrier, however, is inaccessibility of metastatic tissue. A potential solution is to characterize circulating tumor cells (CTCs), but this requires overcoming the challenges of isolating rare cells and sequencing low-input material. Here we report an integrated process to isolate, qualify and sequence whole exomes of CTCs with high fidelity, using a census-based sequencing strategy. Power calculations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
457
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(483 citation statements)
references
References 42 publications
14
457
2
4
Order By: Relevance
“…Most of the MS panel is designed for (A) MSs of type AC on the X Chromosome to allow for monoallelic MS calling Wasserstrom et al 2008;Reizel et al 2011;Segev et al 2011;Shlush et al 2012) and for (B) the longest MS loci possible, which exhibit a higher mutation rate in vivo (Ellegren 2004;Supplemental Table S2). Notably, primers were designed such that the entire MS will be covered within a 150-bp Examples of single-cell analyses to reconstruct clonal/lineage analysis Wang et al 2012;Xu et al 2012;Gawad et al 2014;Lohr et al 2014;Lodato et al 2015) (Navin et al 2011;Cai et al 2014;Wang et al 2014) ) Salipante et al 2010;Reizel et al 2011Reizel et al , 2012Shlush et al 2012;Evrony et al 2015) read (see Methods). (2) We modified the second PCR to apply a sample barcode by utilizing combinations of forward and reverse PCR primer combinations, resulting in a dual indexed NGS library (Supplemental Fig.…”
Section: A Generic Cell Lineage Analysis Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the MS panel is designed for (A) MSs of type AC on the X Chromosome to allow for monoallelic MS calling Wasserstrom et al 2008;Reizel et al 2011;Segev et al 2011;Shlush et al 2012) and for (B) the longest MS loci possible, which exhibit a higher mutation rate in vivo (Ellegren 2004;Supplemental Table S2). Notably, primers were designed such that the entire MS will be covered within a 150-bp Examples of single-cell analyses to reconstruct clonal/lineage analysis Wang et al 2012;Xu et al 2012;Gawad et al 2014;Lohr et al 2014;Lodato et al 2015) (Navin et al 2011;Cai et al 2014;Wang et al 2014) ) Salipante et al 2010;Reizel et al 2011Reizel et al , 2012Shlush et al 2012;Evrony et al 2015) read (see Methods). (2) We modified the second PCR to apply a sample barcode by utilizing combinations of forward and reverse PCR primer combinations, resulting in a dual indexed NGS library (Supplemental Fig.…”
Section: A Generic Cell Lineage Analysis Platformmentioning
confidence: 99%
“…5, see below). We thus opted to evaluate the platform on cancerous cells, which harbor microsatellite instability (MSI), as cancer is the major application of clonal analysis and cell lineage reconstruction (Ding et al 2012;Gawad et al 2014;Lohr et al 2014;Wang et al 2014). We designed a novel controlled ex vivo experiment utilizing DU145, a human male prostatic carcinoma cell line, via an automated cell picking device (CellCelector, ALS) ( Fig.…”
Section: Cell Lineage Tree Of Ex Vivo Grown Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the rise of rapid genome-sequencing techniques has made it practical to translate this concept to the clinic. Three main approaches are being pursued: analysing circulating tumour DNA 1 , examining whole tumour cells in the bloodstream 2 and capturing small vesicles called exosomes that are ejected by tumours 3 (see 'Scalpel-free biopsies'). And scientists have found that blood platelets might be able to offer up cancer clues, too (see 'Platelets ingest tumour data').…”
mentioning
confidence: 99%
“…Circulating epithelial cells (CECs) of pancreatic origin have been found in the blood of pancreatic cyst patients, and may enable the early detection of pancreatic cancer . Finally, circulating tumor cells (CTCs), which are shed from a primary tumor into the circulatory system and are thought to contribute to metastasis (Maheswaran and Haber 2010), can inform patient prognosis (Cristofanilli et al 2004), therapeutic efficacy Stott et al 2010), and the genetics of disseminating cancer cells (Russnes et al 2010;Navin et al 2011;Pratt et al 2014;Lohr et al 2014). A challenge in studying these cells is that they are exceedingly rare-as few as 1 CTC per 100 million blood cells, for example (Racila et al 1998;Krivacic et al 2004)-requiring engineered solutions to isolate as many of the target cells as possible, while capturing few blood cells.…”
Section: Introductionmentioning
confidence: 99%